The Shadow of Homosexuality Hovers over Macedonia: Сеништето на хомосексуалноста кружи над Македонија - Trajanoski, Žarko; Bužarovska, Rumena (Identities: Journal for Politics, Gender and Culture, 2005)
Author(s): Žarko Trajanoski | Жарко Трајаноски Title (English): The Shadow of Homosexuality Hovers over Macedonia Title (Macedonian): Сеништето на хомосексуалноста кружи над Македонија Translated by (Macedonian to English): Rumena Bužarovska | Румена Бужаровска Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 4, No. 1-2 (Summer - Winter 2005) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 201-239 Page Count: 39 Citation (English): Žarko Trajanoski, “The Shadow of Homosexuality Hovers over Macedonia,” translated from the Macedonian by Rumena Bužarovska, Identities: Journal for Politics, Gender and Culture, Vol. 4, No. 1-2 (Summer - Winter 2005): 201-239. Citation (Macedonian): Жарко Трајаноски, „Сеништето на хомосексуалноста кружи над Македонија“, Идентитети: списание за политика, род и култура, т. 4, бр. 1-2 (лето - зима 2005): 201-239.